2014
DOI: 10.1016/j.anifeedsci.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of commercial selenium products on glutathione peroxidase activity and semen quality in stud boars

Abstract: a b s t r a c tThe aim of this study was to determine how dietary supplementation of inorganic and organic selenium affects the selenium concentration and glutathione peroxidase activity in blood and sperm of sexually mature stud boars. Twenty-four boars of the Large White, Landrace, Pietrain and Duroc breeds of optimal breeding age (on average 2.5 years old) were used. The study lasted 90 days. The boars were randomly assigned to one of three dietary treatment groups: T1 = control; no added selenium (n = 8 bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
22
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 37 publications
7
22
1
3
Order By: Relevance
“…Our findings were consistent with Petrujkic et al (2014), who determined high GSH-Px activity in blood plasma of boars after Se supplementation. Our findings were consistent with Petrujkic et al (2014), who determined high GSH-Px activity in blood plasma of boars after Se supplementation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings were consistent with Petrujkic et al (2014), who determined high GSH-Px activity in blood plasma of boars after Se supplementation. Our findings were consistent with Petrujkic et al (2014), who determined high GSH-Px activity in blood plasma of boars after Se supplementation.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, minute fluctuations of trace mineral levels significantly affect biological functions (Navarro-Alarcon & Cabrera-Vique 2008). Selenium (Se), an essential trace element, is necessary for reproduction, immunity, antioxidant systems, embryonic growth and other physiological functions (Ahsan et al 2014;Petrujkic et al 2014). Selenium (Se), an essential trace element, is necessary for reproduction, immunity, antioxidant systems, embryonic growth and other physiological functions (Ahsan et al 2014;Petrujkic et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This might be due to the reason that organic Se as a good source of Se, could be utilized by animals in a more effective way, transported and retained in a good order in target tissues or organs compared to the inorganic Se. Similar findings were reported in rams (Berry et al ), buffalo (El‐Siefy ) and boars (Faye et al ; Petrujkic et al ). Moreover, in goats Kumar et al () reported that Zn and Se levels in blood serum and seminal plasma increased significantly ( P > 0.05) at 60, 75, 90 and 105 days as compared to day 0 in the tested group.…”
Section: Discussionsupporting
confidence: 86%
“…In lambs, organic Se sources (such as selenized yeast and Se-enriched probiotics) are more effective than inorganic Se sources (sodium selenite) in increasing tissue and blood Se Yu-xuan Song and Jin-xing Hou contributed equally to this work. 1 concentrations as well as increasing GSH-Px activitiy in the blood [21]. The dose range, within which the dietary Se supplementation of mature ewes increased blood Se concentrations, was more limited for inorganic Na-selenite than for organic Se-yeast [22].…”
Section: Introductionmentioning
confidence: 93%
“…Previous studies have shown that Se has an important biochemical function in erythrocyte glutathione peroxidase activity (GSH-Px) [1,2]. Se promotes proper gait [3], healthy pregnancies [4,5], and growth [6,7] in animals.…”
Section: Introductionmentioning
confidence: 99%